The Making of ADHD: A Comparative Content Analysis of Teachers’ and Doctors’ Worldviews - Dominik Robin; Michael Gemperle; Michael von Rhein; Frank Wieber; Hotz, Sandra (My University, 2022)
Little is known about how teachers and doctors make sense of ADHD. Drawing on a corpus of online accounts, we reconstructed their worldviews with a qualitative analysis. While both professional groups referred to a male troublemaker and to the German literary figure of the Fidgety Phil, they also expressed rival expert claims. Doctors represented the scientific authority in labeling and diagnosing ADHD, whereas teachers attached objective meaning to the medical judgement by pathologizing deviant behavior and justifying measures of control.

Darüber, wie Lehrpersonen und medizinische Fachpersonen ADHS verstehen, ist wenig bekannt. Die Analyse von Online-Narrationen hat gezeigt, dass beide Berufsgruppen auf einen männlichen Unruhestifter und die literarische Figur des Zappelphilipps Bezug nahmen und rivalisierende Expertenansprüche äusserten. Medizinische Fachpersonen repräsentierten die Autorität bei der Etikettierung und Diagnosestellung, während Lehrpersonen dem medizinischen Urteil objektive Bedeutung beimassen, indem sie auffälliges Verhalten pathologisierten und damit die Anwendung pädagogischer Massnahmen begründeten.

On connaît mal la façon dont les enseignants et médecins comprennent le diagnostic du TDAH. À partir de témoignages en ligne, nous avons reconstitué leurs visions du monde. L’analyse qualitative montre que les deux groupes professionnels font référence à un perturbateur masculin et à la figure littéraire allemand de Philippe le Balanceur, sur fond d’une rivalité d’expertise. Les médecins s’attribuent l’autorité scientifique du diagnostic tandis que les enseignants attachent au jugement médical un sens objectif en pathologisant les comportements déviants et en justifiant des mesures de contrôle.
Keywords: ADHD; social construction; mental illness; mental health literacy; content analysis